Lagoonal settlements and relative sea level during Bronze Age in Northern Adriatic: Geoarchaeological evidence and paleogeographic constraints. (22nd May 2017) - Fontana, A.; Vinci, G.; Tasca, G.; Mozzi, P.; Vacchi, M.; Bivi, G.; Salvador, S.; Rossato, S.; Antonioli, F.; Asioli, A.; Bresolin, M.; Di Mario, F.; et al.
Abstract: The study of archaeological structures has been widely applied in the Mediterranean to infer the past relative sea level (RSL), but the use of Prehistoric sites was generally scarce. Pre-Classical settlements related to past marine position are quite rare and, after their occupation phase the landscape has often dramatically changed. A peculiar situation characterizes the NW Adriatic coast, along the lagoon fringe east of Venice, where several Bronze-Age settlements have been exposed after the land reclamation carried out in the 20 th century. We analyzed the published information and collected new stratigraphic and geochronological data in five major sites where index points related to past sea-level are recorded. This research investigated in detail the geomorphological and geoarchaeological aspects, allowing to distinguish three different typologies of settlements: a) sites on Holocene fluvial ridges; b) sites on the alluvial plain of the Last Glacial Maximum (LGM) and along groundwater-fed rivers entering in the lagoon; c) sites in the lagoon, controlling key locations. The lagoonal environment had an extent rather comparable to the modern one already 4000–3500 years BCE, when sea level was above −4 m respect mean sea level (MSL). In the second part of the early Bronze Age, around 1800 BCE, the observed RSL was between −3.0 and −2.7 m MSL, while at the transition between recent and final Bronze Age (1250–1100 BCE) it probably was at −2.0 ± 0.6 m MSL. The analyzed settlements were abandoned during the final Bronze Age, but the data testify that sea level rose progressively. This suggests that the abandonment was probably not primarily due to RSL, but to socio-cultural reasons or other environmental causes that are not yet well understood by the archaeological community.